TASAWUF FALSAFI - Wahdi Sihombing (Jurnal At-Tabayyun, 2020)
The philosophers of Islam there are legitimate people referred to as disciples of Al Farabi and his great caliph, then without disputputity he is Ibn Sina. To the extent that we apply to Ibn Sina some opinions, when in fact the opinion comes from Al Farabi. Ibn Sina's closeness to Al Farabi's thoughts on the fact that Ibn Sina explained his cleverness to understand Al Farabi's mindset and explain it, to the extent that the explanation never came out of Al Farabi himself. Much of Al Farabi's strange and vague thoughts can be evident in the hands of Ibn Sina. If Ibn Rushd was Aristotle's translator in the philosophy of drama, then Ibn Sina was al Farabi's translator proficient in Islamic philosophy. On the other hand it is mentioned that a person is called a Sufi because they are at the forefront (shaff) before Allah, through the exaltation of martyrs to Him.